Estimulación temprana para el desarrollo cognitivo - Suasnavas Pichucho, Arianna Pamela (2016)
This research is about "Early stimulation for cognitive development" to be applied at Hermano Miguel school. The early stimulation gives advantage to develop the senses and abilities in children in their first years of life, and also it provides a variety of activities with scientific and applied base. This research has a social impact such us help children and their parents to develop the abilities and cognitive skills, the main objective consisted to turn early stimulation into a pleasant routine to have a good relationship between parents and children. This research shows that if we provide to children early stimulation in their first years of life, they will be competitive and cooperative and active to face different situations in their own life and the surroundings. During the development of this research, it will take into account the given objectives to know how it affects the early stimulation in the cognitive development in children. After the data analysis from interviews, surveys and observation sheets, it was obtained relevant information in order to know the importance of early stimulation in cognitive development in children under four years old. Positively encourage to the children also is to educate correctly. Early education enhances the brain, for that reason the early education is based to know and focus the educational effort according to the children ages and encourage them properly.